Frequency of Susceptibility to Cefiderocol in Carbapenem-Resistant Gram-Negative Bacteria by Kirby-Bauer Disc Diffusion Method; A Study in Tertiary Care Hospital of Southern Punjab - Zainab, Maha; Inam Ullah Khan; Fizza Fatima (Journal of Postgraduate Medical Institute, 2025)
<!–StartFragment –> Objective: The study was planned to assess the frequency of susceptibility to Cefiderocol in carbapenem-resistant gram-negative bacteria using the Kirby-Bauer disc diffusion method. Methodology: This was a cross-sectional study conducted at the Department of Microbiology, Combined Military Hospital, from 1st July to 31st December 2024. A total of 101 specimens submitted to the department and growing carbapenem-resistant gram-negative rods were included consecutively; duplicate specimens were excluded. Specimens—including urine, blood, pus, respiratory samples, and body fluids—were processed using conventional methods. Organisms were identified by colony morphology, microscopic features, biochemical tests, and API-10S. The Kirby-Bauer disc diffusion method was performed on Cation-Adjusted Mueller-Hinton agar plates according to CLSI guidelines. Cefiderocol disk diffusion was applied on both commercially prepared CAMH-agar plates and manually produced ID-CAMH-agar plates. Data were analyzed using SPSS version 23 with descriptive statistics and Fisher's exact test to assess Cefiderocol sensitivity across demographic strata. Results: The mean age of patients was 42.6 ± 14.3 years, with 55.4% males and 70.3% indoor cases. Pus (28.7%), urine (26.7%), and blood (23.8%) were the most common specimen types. Enterobacterales (66.3%) and Pseudomonas aeruginosa (21.8%) were frequently isolated. Cefiderocol sensitivity was observed in 77.2% of isolates, while resistance was noted in 17.8%. Conclusions: Cefiderocol demonstrates a high level of activity against carbapenem-resistant gram-negative microorganisms, supporting its clinical utility in effectively managing severe and complex infections. These findings highlight Cefiderocol as a promising therapeutic option.<!–EndFragment –>